Examining the role of ChatGPT in promoting health behaviors and lifestyle changes among cancer patients - Fahad Alanezi
Purpose: This study aims to investigate the role of ChatGPT in promoting health behavioral changes among cancer patients. Methods: A quasi-experiment design with qualitative approach was adopted in this study, as the ChatGPT technology is novel, and many people are unaware of it. The participants included outpatients at a public hospital. An experiment was carried out, where the participants used ChatGPT for seeking cancer related information for two weeks, which is then followed by focus group (FG) discussions. A total of 72 outpatients participated in ten focus groups. Results: Three main themes with 14 sub-themes were identified reflecting the role of ChatGPT in promoting health behavior changes. Its prominent role was observed in developing health literacy, promoting self-management of conditions through emotional, informational, motivational support. Three challenges including privacy, lack of personalization, and reliability issues were identified. Conclusion: Although ChatGPT has a huge potential in promoting health behavior changes among cancer patients, its ability is minimized by several factors such as regulatory, reliability, and privacy issues. There is a need for further evidence to generalize the results across the regions.